Species morphospace boundary revisited through wing phenotypic variations of Antodynerus species (Hymenoptera: Vespidae: Eumeninae) from the Indian subcontinent - Anand, P. P.; Seena, S.; Girish Kumar, P.; Shibu Vardhanan, Y. (Frontiers in Ecology and Evolution, 2023)
The main objective of the present paper was to investigate the taxonomic significance of wing phenotypic variations (size and shape) for classifying potter wasps. This is the first study investigating the wing size and shape variations, as well as wing asymmetry, sexual dimorphism, wing integration, and phylogenetic signal analysis of all known Antodynerus species from the Indian Subcontinent: A. flavescens, A. limbatus, and A. punctatipennis. We used forewings and hindwings for Geometric morphometric analysis and we proved that each species’ wing had unique size and shape variations, as well as significant right-left wing asymmetry and sexual dimorphism across the Antodynerus species, as verified by Discriminant function analysis. Wings of Vespidae are longitudinally folded; based on that, we tested two alternative wing modular hypotheses for evaluating the wing integration, using two subsets organization, such as anterior-posterior (AP) and proximal-distal (PD) wing modular organization. We proved that Antodynerus species wings are highly integrated units (RV>0.5), and we rejected our hypothesis at p< 0.05. The morphospace distribution analysis revealed that each species has its unique morphospace boundary, although they share some level of homoplasy; which suggest to us that we can use wing morphometric traits for Antodynerus species delimitation. In addition, we revealed the phylogenetic signal of Antodynerus species. Surprisingly, we found a shape-related phylogenetic signal in the forewing, and there is no significant (p>0.05) phylogenetic signal in forewing size, hindwing shape, and size. We observed that Antodynerus species forewing shape is evolutionarily highly constrained than the hindwing. We found that A. limbatus and A. flavescens with distinct geographical distribution, share a similar evolutionary history, while A. punctatipennis independently evolved.